Intramural Esophageal Hematoma Mimicking Acute Coronary Syndrome: Complication of Warfarin Use in a Mechanical Heart Valve Patient - Toktam Alirezaei; Rana Irilouzadian; Ali Pirsalehi; Sayyed Mojtaba Nekooghadam (Case Reports in Medicine)
A 59-year-old female with a history of mitral valve replacement presented to emergency department, complaining of sudden-onset retrosternal chest pain since 4 hours ago. Electrocardiogram, laboratory tests, and computed tomography (CT) angiography of aorta were performed and ruled out aortic dissection and cardiovascular events. However, new complaint of odynophagia, dysphagia, and incidental findings in CT angiography proposed esophageal pathologies. After initial workup including upper gastrointestinal endoscopy, intramural esophageal hematoma was diagnosed. Laboratory tests revealed significant reduction in the hemoglobin level. Management of warfarin-induced major bleeding in a patient whom anticoagulation was necessary for the prevention of mechanical heart valve thrombosis was challenging. The patient recovered fully with conservative treatment and was discharged on hospital day 14 with low molecular weight heparin. We described a case of intramural esophageal hematoma as a rare condition that could be misdiagnosed as a cardiovascular emergent disease and would be worsened by antiplatelet and anticoagulation therapy. Accordingly, it is important to differentiate intramural esophageal hematoma from cardiac ischemic events. Another challenge was correction of coagulation in the presence of mechanical mitral valve. Fortunately, we had a favorable outcome following conservative management.